2006
DOI: 10.1002/hipo.20173
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of hippocampal estrogen synthesis causes region-specific downregulation of synaptic protein expression in hippocampal neurons

Abstract: Previous studies have shown that synapses and expression of synaptic proteins in hippocampal neurons are regulated by hippocampus-derived estradiol. Here, we compared the effects of this paracrine regulation in different hippocampal regions. In tissue sections, immunohistochemistry followed by semiquantitative image analysis revealed a three-fold higher expression of steroidogenic acute regulatory protein (StAR) and aromatase in neurons of the CA3 than that of the CA1 region and in granule cells. Next, we trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
62
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 99 publications
(69 citation statements)
references
References 26 publications
7
62
0
Order By: Relevance
“…After 4 DIV, the incubation media were supplemented with letrozole (10 Ϫ7 M; kindly provided by Novartis) and letrozole plus 17 ␤-estradiol (10 Ϫ7 M, water soluble, Sigma-Aldrich) for 7 d. To test time-dependency, the effect of letrozole was additionally tested for various time intervals. Letrozole did not affect the viability of the cultures, as tested in previous experiments Prange-Kiel et al, 2006).…”
Section: Experiments Using Hippocampal Slice Culturessupporting
confidence: 66%
“…After 4 DIV, the incubation media were supplemented with letrozole (10 Ϫ7 M; kindly provided by Novartis) and letrozole plus 17 ␤-estradiol (10 Ϫ7 M, water soluble, Sigma-Aldrich) for 7 d. To test time-dependency, the effect of letrozole was additionally tested for various time intervals. Letrozole did not affect the viability of the cultures, as tested in previous experiments Prange-Kiel et al, 2006).…”
Section: Experiments Using Hippocampal Slice Culturessupporting
confidence: 66%
“…We also provide a novel mechanism for morphine action: induction of estradiol release by neurons, which is protective against iA␤ toxicity in our case. Although estrogen secretion by hippocampal neurons is described previously (Kretz et al, 2004;Prange-Kiel et al, 2006, 2008, this is the first time, to our knowledge, that induction of estradiol release in hippocampal neurons by morphine is reported. The efficacy of estrogen replacement therapy has been debated for a long time, and cognitive function is not necessarily improved after the therapy (Birge, 1996;Schneider and Finch, 1997;Mulnard, 2000;LeBlanc, 2002).…”
Section: Discussionmentioning
confidence: 60%
“…Interestingly, a number of studies have also demonstrated that aromatase is located in postsynaptic structures (Naftolin et al, 1996;Kretz et al, 2004;Prange-Kiel et al, 2006). These data suggest that estrogens may be produced on either side of the synapse.…”
Section: Synaptic Localization Of Aromatasementioning
confidence: 96%